PHBS: HEALTHY MADRASA PROGRAM IMPLEMENTATION THROUGH ONE MAN ONE TREE AND BRI ACTIVITIES - M Kamal; Nadhilah Ishmah; Maryana (International Jurnal of Education Schoolars, 2020)
Healthy madrasah program which includes One Man One Tree and BRI or clean, neat and beautiful activities intended to teach students to live clean, neat and beautiful. This activity is one way that schools do to instill the value of clean and healthy living characteristics to every student at MAN Insan Cendekia Jambi. This study aims to 1) Describe the Implementation of the Healthy Madrasah Program through the One Man One Tree and BRI Activities in MAN Insan Cendekia Jambi to create a Clean and Healthy Life Behavior, 2) Knowing the effectiveness of the Implementation of the Healthy Madrasah Program through the One Man One Tree and BRI Activities in MAN Insan Jambi Scholar to create Clean and Healthy Behavior. The research method used is a mix method with data collection techniques using interviews, questionnaires and documentation. Data analysis was performed using Descriptive Statistics and Triangulation techniques. The findings of this study are: 1) Environmental Conditions MAN Insan Scholar Jambi before the existence of the Healthy Madrasah program has been arranged but still not neatly arranged, the environmental conditions are still very arid. After the existence of the Madrasah Healthy program the MAN Insan Scholar environment was neatly organized, and the environment was no longer arid because many plants were planted, especially productive plants, 2) The application of activities contained in the healthy madrasah program created the character of clean and healthy life behavior among students, 3) Healthy Madrasah Program through One Man One Tree and BRI to create Clean and Healthy Life Behavior for Students is effective because it has been embedded in the daily behavior of students, 4) Percentage of effectiveness of the Implementation of Healthy Madrasah Program through One Man One Tree and BRI Activities in MAN Jambi Scholar Insan to create a Clean and Healthy Life Behavior with an accuracy measurement of 85% is considered very effective.